Do children with developmental dyslexia have syntactic awareness problems once phonological processing and memory are controlled? - Robertson, Erin K.; Mimeau, Catherine; Deacon, S. Hélène (Frontiers in Language Sciences, 2024)
Introduction Syntactic awareness is the ability to monitor and manipulate word order within sentences. It is unclear whether children with dyslexia have syntactic awareness problems, as there are mixed results in the literature. Dyslexia is typically classified with very poor word and nonword reading and phonological processing problems are often observed in this population. It is conceivable that a phonological deficit could strain memory when performing oral syntactic awareness tasks. Here we examine if syntactic awareness problems are observed in children with dyslexia once phonological processing and memory skills are controlled. Methods Real and nonword reading efficiency tests determined reading level. Children with dyslexia (n = 25) were compared to typically developing children (n = 24) matched for age (M = 8;8) and nonverbal abilities. Syntactic awareness was measured with an oral word order correction task (e.g., Is baking Lisa and her son in his room sleeps). Tests of phonological awareness, phonological memory, and verbal working memory were also administered and served as controls. Results The dyslexic group performed worse than typically developing readers on syntactic awareness and this group difference persisted once phonological memory and verbal working memory were controlled. However, after controlling for phonological awareness skills, there were no group differences on the syntactic awareness test. Discussion: The results suggest that phonological awareness problems in particular might be responsible for syntactic awareness difficulties in dyslexia and future studies should control for this. The results are discussed within theoretical frameworks on the nature of oral language deficits in dyslexia.